Efficient photocatalytic degradation of industrial dye using biogenic ZnO NPs. (2022) - Singh, Karanpal; Nancy,; Singh, Jagpreet; Singh, Gurjinder
Graphical abstract: Abstract: Water pollution reduction and the development of a cost-effective and sustainable platform for its abatement are incessant challenges in today's world. In this regard, the current study describes the formation of zinc oxide nanoparticles (ZnO NPs) via a green/sustainable, cost-effective approach using syzygium cumini leaves and their photocatalytic activity to counter the above-stated problem. The shape, structure, crystallite size, and optical properties of the NPs were all determined using various characterizations FE-SEM, UV–Vis Spectroscopy, XRD, EDX, and FTIR. XRD study revealed that synthesized ZnO NPs are spherical shaped polycrystalline with wurtzite hexagonal structure, with an average crystallite size of 29 nm. The UV–vis absorption spectra at 380 nm revealed the reduction of the precursor into ZnO NPs. FTIR study investigated the surface adsorption of functional groups on NPs. Furthermore, prepared biogenic ZnO NPs showed remarkable photocatalytic degradation potential towards reactive orange-4 (RO-4) dye with dosage variation. 93.9% degradation efficiency was achieved with a 15 mg dosage. Therefore, this research contributes to the development of green/sustainable photocatalysts for environmental remediation.